Sociocultural pressure: a model of body dissatisfaction for young women - Silva, Wanderson Roberto da [UNESP]; Barra, Julia Valerio [UNESP]; Neves, Angela Nogueira; Maroco, Joao; Duarte Bonini Campos, Juliana Alvares [UNESP] (Cadernos Saude Publica, 2020)
The aim of the study was to verify the influence of pressure from sociocultural agents on dissatisfaction with face and body in young women mediated by the internalization of the lean and muscular body and to identify the contribution of individual characteristics to this model. A total of 612 university female students participated of study. The students completed the Portuguese versions of the Sociocultural Attitudes Towards Appearance Questionnaire-4 and of the Body Area Scale-Revised and a sociodemographic questionnaire. A hypothetical model was constructed using structural equation modeling to test the relationship between the variables. The model fit and the significance of the hypothetical paths were verified. The results provide evidence that the greater the pressure of sociocultural agents and the internalization of the lean body, the more women were dissatisfied with body and face appearance. The media contributed to a greater internalization of the muscular body, which reduced the body dissatisfaction. The practice of physical activity and a higher economic level contributed to a greater internalization of the muscular body, which reduced body dissatisfaction. A higher economic level also influenced the internalization of the lean body and increased the dissatisfaction with face and body. A higher body mass index contributed to a greater pressure from sociocultural agents, greater internalization of the lean body, and greater dissatisfaction with body and face. The relationships identified in the model can contribute to the development of strategies aimed at reducing body dissatisfaction and eating disorders in the population, such as body acceptance.
Keywords: Body Image; Body Dissatisfaction; Women